Content Analysis of Gift Advertisements - Mahajan , Drishti (Gyan Management Journal, 2023)
The objective of this study is to conduct a content analysis of gift themed advertisements that appear in the Indian print media. It seeks to contribute to the neglected area of gift advertising by seeking to understand the practitioners use of the gift theme. Three coders were trained to analyse advertisements on select criteria culled from gifting literature viz., type of product, type of relationship, gift-giving occasion, type of emotional appeal, verbal and visual cues and gender portrayal. The study reveals the limited popularity of the gift theme as a complete years vigil on two popular media vehicles resulted in only 53 usable advertisements. On the elements of type of product featured and gift giving occasion the results are as expected but they are contrary to literature on all the other variables. There is evidence of lack of variety in the use of the gift theme in advertisements. This theory- practice gap in yet another area of marketing is potentially worrisome and the possible reasons for it forwarded in this research need to be verified by future researchers.